Management and Socio-economic Aspects of Livestock Farming in Flood-prone Areas of Cuddalore District - Silambarasan, P.; Vannan, T. T.; Churchil, Richard; Vengadabady, N.; Saravanan, K. P.; Kannadhasan, M. S.; Vasudevan, S. (International Journal of Bio-resource and Stress Management, 2025)
A detailed survey was conducted from September, 2020 to February, 2021 to document the socio-economic status and livestockrearing practices in the flood-prone areas of Cuddalore district. This study assessed the socio-economic profile, livestock holdings, housing practices, stocking density, and feeding management of livestock farmers in flood-prone areas of Cuddalore district, Tamil Nadu. Floods, among the major natural disasters affecting agriculture and livestock-based livelihoods in coastal regions of India. A total of 600 households (20 villages×30 farmers) were surveyed across three Geographical Areas (GGA I: 0–10 m, GGA II: 11–20 m, GGA III: >20 m above mean sea level). Results revealed a predominance of male farmers (63.83%) with an overall literacy rate of 64.48%, lower than the district average. Most farmers were daily wage labourers (65.17%) and had landholdings below one acre, with 33% landless. Thatched-roof housing was the most common (49.17%), and a significant proportion of farmers (40.16%) lacked any animal shelter. Livestock holdings were generally small, with non-descriptive cattle and goats predominating, and significant variations were observed in crossbred cow, goat, and sheep numbers across GGAs. The mean number of animals shed-1 ranged from 9.67 to 12.27, with higher stocking densities in GGA II. Regular concentrate feeding averaged 1.20 kg day-1, increasing to 3.81 kg day-1 after floods to support recovery. The study highlighted that low literacy, small landholdings, and limited infrastructure constrained adaptive capacity among livestock farmers. These findings underscored the need for targeted extension services, flood-resilient animal housing, and improved feeding strategies to enhance livestock resilience in flood-prone areas.